EKSEKUSI OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - JAMES RIDWAN EFFERIN (Yuriska: Jurnal Ilmiah Hukum, 2020)
ABSTRACTOn the 6th day of January 2020, the Constitutional Court of the Republic of Indonesia has issued a Decree Number 18/PUU-XVII/2019 (“the Constitutional Court Decree”), which decides that regarding the phrase “has an equal enforceable power as the court decisions that have permanent legal force” on Article 15 Paragraph (2) of the Law number 42 year 1999 on Fiduciary (“the Law No. 42/1999”), is in contradiction with the 1945 Constitution of the Republic of Indonesia and shall have no legal binding power if it is not considered to be “towards any fiduciary that have no consent on default and the debtor has raised an objection to surrender the fiduciary object voluntarily. Furthermore the phrase “default” on Article 15 Paragraph (3) of the Law No. 42/1999 is in contradiction with the 1945 Constitution of the Republic of Indonesia and shall have no legal binding power if it is not considered to be “a default shall not be determined solely by the creditor, but should be based on a consent between the creditor and debtor or based on any legal actions which determine the said default.”The Constitutional Court gives a legal interpretation that the executorial power of the Fiduciary Certificate is not considered automatically being applicable, but it shall depend on certain condition(s), i.e.: a consent on default by the creditor and debtor, and /or the willingness of the debtor to voluntarily surrender its fiduciary objects. This Decree will give an impact to the creditor because Fiduciary is supposed to have a character of ease on the execution if the debtor is in default (Elucidation of Article 15 Paragraph (3) Law No. 42/1999), but now if the debtor refused to cooperate, then the creditor should have a decree from the Court first before executing any fiduciary object.The type of this legal research is juridical normative with a legal and conceptual approaches. Keywords: Constitutional Court Decree No. 18/PUU-XVII/2019; Execution; Fiduciary ABSTRAK  Pada tanggal 6 Januari 2020 Mahkamah Konstitusi Republik Indonesia telah mengeluarkan Putusan Nomor 18/PUU-XVII/2019 (“Putusan Mahkamah Konstitusi”)  yang menentukan bahwa frasa “kekuatan eksekutorial” dan “sama dengan putusan pengadilan yang berkekuatan hukum tetap” pada Pasal 15 Ayat (2) Undang-Undang Nomor 42 Tahun 1999 tentang Jaminan Fidusia (“UU No. 42/1999”), bertentangan dengan UUD 1945 dan tidak mempunyai kekuatan hukum mengikat sepanjang tidak dimaknai “terhadap jaminan fidusia yang tidak ada kesepakatan tentang cidera janji dan debitur keberatan menyerahkan secara sukarela objek yang menjadi jaminan fidusia. Selain itu frasa “cidera janji” pada Pasal 15 Ayat (3) UU No. 42/1999 juga dinyatakan bertentangan dengan UUD 1945 dan tidak mempunyai kekuatan hukum mengikat sepanjang tidak dimaknai bahwa “adanya cidera janji tidak ditentukan secara sepihak oleh kreditur melainkan atas dasar kesepakatan antara kreditur dengan debitur atau atas dasar upaya hukum yang menentukan telah terjadinya cidera janji.”Mahkamah Konstitusi telah memberikan penafsiran hukum bahwa kekuatan eksekutorial Sertifikat Jaminan Fidusia tidak serta merta dapat diberlakukan, namun digantungkan pada suatu keadaan tertentu, misalnya: kesepakatan cidera janji oleh kreditur dan debitur, dan/atau kesediaan debitur untuk menyerahkan objek jaminan fidusia dengan sukarela.Keputusan ini memberikan dampak kepada kreditur karena seharusnya Jaminan Fidusia mempunyai sifat mudah dalam eksekusi apabila debitur wanprestasi (Penjelasan Pasal 15 Ayat (3) UU No. 42/1999), tetapi saat ini apabila debitur menolak bekerjasama, maka kreditur harus memperoleh putusan pengadilan lebih dahulu sebelum melakukan eksekusi.Tipe penelitian hukum ini adalah yuridis normatif dengan menggunakan pendekatan undang-undang dan pendekatan konseptual. Kata Kunci: Putusan Mahkamah Konstitusi 18/PUU-XVII/2019; Eksekutorial; Fidusia